How do you solve (x - 2) ^ { 2} + 3= 4?
2 Answers
Apr 28, 2018
Explanation:
first expand the quadratic equation
then sum all the unknown and the constant which will give you
then factorise the equation and u get
therefore
Apr 28, 2018
Explanation:
"isolate "(x-2)^2" by subtracting 3 from both sides"
rArr(x-2)^2=4-3=1
color(blue)"take the square root of both sides"
sqrt((x-2)^2)=+-sqrt1larrcolor(blue)"note plus or minus"
rArrx-2=+-1
"add 2 to both sides"
rArrx=2+-1
rArrx=2-1" or "x=2+1
rArrx=1" or "x=3